STUDY OF ARCHITECTURAL CONCERNS ON DESIGN PRINCIPLES IN THE CATHOLIC CHURCH OF PURBALINGGA - Yohanes Wahyu Dwi Yudono; Susatyo Adhi Pramono (Teodolita ( Media Komunikasi Ilmiah di Bidang Teknik ), 2019)
Overall, the shape of the Purbalingga Catholic church building displays the style / style of Javanesearchitecture (Joglo). However, in an effort to "adopt" the architectural appearance, additional forms weremade to obtain vernacular architectural works, which grew out of architectural relics that had been knownin life in the community. Buildings (in this case the church), are inanimate objects, but that does not meanthat buildings are not "soulless". The church that is built is intended for humans, therefore must berespected by humans, by character and tendencies, by their passions and ideals (YB. Mangunwijaya, 1988).Observations made on the object of study (in this case the Catholic church in Purbalingga), basedon KWSmithies (1982), where human consideration as a basis for design can be in the form of severaldesign principles that are interrelated with each other, namely: design principles aspects of view,breathing, hearing, temperature, humidity, and design principles of human movement aspects.Keywords: Architectural Details, design principles, Forms of Architecture.ABSTRAKSecara keseluruhan, bentuk bangunan gereja Katolik Purbalingga menampilkan gaya / langgamarsitektur Jawa (Joglo). Namun, dalam usaha â€œmengadopâ€ tampilan arsitekturnya, dilakukan penambahanpenambahanbentuk guna mendapatkan karya arsitektur yang vernakular, yang tumbuh dari peninggalanarsitektur yang telah dikenal dalam kehidupan dimasyarakat.Â  Bangunan (dalam hal ini gereja), merupakanbenda mati, namun tidak berarti bangunan tidak â€œber-jiwaâ€. Gereja yang dibangun diperuntukan bagimanusia, oleh karena itu harus dinafasi oleh manusia, oleh watak dan kecenderungan-kecenderungan, olehnafsu dan cita-citanya (YB. Mangunwijaya, 1988).Pengamatan yang dilakukan terhadap objek kajian (dalam hal ini gereja Katolik di Purbalingga),mendasarkan pada K.W.Smithies (1982), dimanaÂ  pertimbangan manusia sebagai basis perancangan dapatberupa beberapa prinsip-prinsip perancangan yang saling berkaitan antara satu dengan yang lain, yaitu:prinsip perancangan aspek pandangan, pernafasan, pendengaran, temperatur, kelembaban, dan prinsipperancangan aspek pergerakan manusia.Kata Kunci: Detil-detil Arsitektur, prinsip-prinsip perancangan, Wujud Arsitektur